Collateral Damaged? Priority Structure, Credit Supply, and Firm Performance - Geraldo Cerqueiro; Steven Ongena; Kasper Roszbach (Norges Bank, 2019)
A unique legal reform in 2004 in Sweden redistributed collateral rights from banks holding floating liens to unsecured creditors without changing the value of assets on firms' balance sheets. Using a country-wide panel of all incorporated firms, we document that a zero-sum redistribution of collateral rights and the resulting reduction in collateral capacity towards banks contracts the amount and maturity of corporate debt and leads firms to slow investment and forego growth. Altering their allocation of assets, firms reduce particularly those assets with a low collateralizable value for banks and also hoard more cash. However, the reform has no impact on corporate capital intensity or efficiency, suggesting that under these newly binding credit constraints firms simply shrink their operations
hdl:11250/2603364
Keywords: D22; G31; G32; 330; collateral; investment; financial constraints; difference-in-differences; floating lien; seniority